Parallel-serial adsorption of phosphate ions by natural sorbents - Сидорчук, Оксана Вікторівна; Мацуська, Оксана Василівна; Сабадаш, Віра Василівна; Гумницький, Ярослав Михайлович (Eastern-European Journal of Enterprise Technologies, 2014)
The process of adsorption of phosphorus compounds on natural sorbent - zeolite, which shows adsorption and ion exchange properties is considered. Phosphates belong to anthropogenic environmental pollutants. They are present in the wastewater of industrial and utility enterprises. Static activity of phosphates in zeolite in their pollution limits in wastewater is investigated. It is shown that they are in low concentrations. This process is described by Henry linear adsorption equation. The presence of other components in the wastewater, especially ammonium compounds, complicates the adsorption process. The absorption of ammonium ions occurs mainly through ion exchange, replacing sodium, potassium and ammonium cations in the zeolite. The absorption of phosphorus compounds proceeds due to adsorption and formation of compounds with calcium and magnesium ions in zeolite pores. Parallel adsorption of two components slightly reduces static activity in relation to phosphorus compounds, but the total adsorption of the two components is higher. The second investigated mechanism of adsorption of components from aqueous solutions by zeolite was serial adsorption. Primarily, adsorption of copper ions, for example, when treating electroplating wastewater was conducted. This process allows to modify sorbent and change its adsorption properties. The next stage was adsorption of phosphate compounds by the modified zeolite, on which these compounds form persistent connections with copper, calcium and magnesium ions, and adsorption capacity of the modified zeolite significantly increases. The studies of parallel and serial sorption indicate the feasibility of these purification methods.